Seeking Justice and Effecting Organizational Change: Kategoria as a Form of Rhetorical Leadership - (:unkn) unknown (My University, 2022)
Organizational scandals at both the institutional and leadership levels abound in society, and, with growing platforms and forums to level allegations, public accusations by myriad individuals have increased. As an understudied genre, kategoria, or speeches of accusation, should be considered for their ability to influence change. In this study, I argue that kategoria can be employed as a form of rhetorical leadership and utilized as a tool to disrupt value hierarchies and, thus, effect organizational change. This investigation assumes a genre analysis to move beyond establishing accusation simply as a classification of forensic rhetoric but to illustrate that the generic form can be employed as rhetorical leadership, able to successfully be used by individuals with varying degrees of power to disrupt value hierarchy expectations and motivate change by establishing guilt and seeking justice. As the evolution of holding those in power accountable for misdeeds and public speeches of accusation continue, this study reveals both the rhetorical tactics that can impact change as well as how those who hold less institutional power can effectively enact these rhetorical strategies to achieve justice. To uncover the rhetorical mechanism of kategoria, I examine three contemporary and successful cases of leadership change in which individuals with less institutional power than the accused used discourse to motivate concrete action. My case studies include accusations leveled at leaders at Michigan State University, Uber, and Facebook. Deeper understanding of kategoria is necessary to enrich scholarship for critics by illuminating the rhetorical strategies that can be successfully deployed in these speeches to accomplish the ends called for by the accuser. Furthermore, elucidating these strategies has practical implications for individuals who wish to reveal leadership transgressions and impact institutional action. Revealing what has been useful in the past can inform future rhetorical attempts at kategoria that call for organizational change. At a time when enhanced understanding of speeches of accusation is critical for scholars and individuals seeking concrete change at the leadership level, my study fuses theoretical and practical implications, impacting both scholarship and society.
Keywords: Accusation; Kategoria; Leadership; Organizational Change; Organizational Communication; Rhetorical Leadership